Analisis Pengaruh Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non Performing Loan (NPL), Biaya Operasional Terhadap Pendapatan Operasional (BOPO), Loan to Deposit Ratio (LDR) dan Size Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Perba - Ismadi, Ismadi; Irawati, Zulfa (Prosiding University Research Colloquium, 2019)
This study aims to analyze the effect of Capital Adequacy Ratio(CAR), Net Interest Margin (NIM), Non Performing Loans (NPL),Operating Costs on Operating Income (BOPO), Loan to DepositRatio (LDR) and Size to Profitability (Case Study in BankingCompanies Listed on the Indonesia Stock Exchange for the 2013-2017 Period). The sampling technique used in this study was apurposive sampling technique with the criteria of Foreign ExchangeConventional Commercial Banks that publish annual financialreports during 2013-2017 on the Indonesia Stock Exchange websiteand the website of each Foreign Exchange Conventional CommercialBank. The method of data analysis in this study with multiple linearregression analysis previously tested the classical assumptions.Hypothesis testing uses t statistical test, F statistic test and coefficientof determination. The results showed that partially showed that theCAR, NPL, LDR, and Size variables had a negative but notsignificant effect on profitability, NIM had a significant positive effecton profitability, and BOPO had a significant negative effect onprofitability. While together the independent variables have an effecton Profitability. The adjusted R square value is 0.913, which meansthat the sixth ability of the independent variable can explainProfitability of 91.3%.